Clinical pharmacist interventions in an intensive care unit reduces ICU mortality at a tertiary hospital in Dubai, United Arab Emirates - Hawra Ali Hussain Alsayed; Fatemeh Saheb Sharif-Askari; Narjes Saheb Sharif-Askari; Rabih Halwani (Elsevier, 2024)
Background: Drug-related problems (DRPs) are prevalent in critical care settings and can be life-threatening. Involving clinical pharmacists (CP) within the critical care team is recommended to optimize therapy and improve patient survival. Objective: To classify DRPs identified by a CP in the Intensive Care Unit (ICU) and to assess the impact of CP interventions accepted by physicians on the length of ICU stay and in-hospital survival. Methods: This study was conducted prospectively at the Medical ICU of Rashid Hospital, a tertiary hospital in Dubai, over a 16-month period from September 2021 to December 2022. The study included patients admitted to ICU during the study period. CP interventions were documented, and DRPs were classified using the modified Pharmaceutical Care Network Europe V.9.1. Results: During the study period, 1004 interventions were recommended for 200 patients. The majority of these interventions, 92% (n = 922), received physician acceptance, and 82% (n = 820) were fully implemented by the physician. In total, 1033 drug-related problems (DRPs) were identified, with a median of 3 DRPs per patient. The most common DRPs was drug selection (61%), followed by dose selection (22%). There were 337 DRPs related to antimicrobial agents. Interestingly, we noted that when we adjusted for patients' demographic data and the Glasgow Coma Scale severity score, patients who received >4 implemented interventions exhibited lower cumulative hazard of death within 90 days of their ICU stay in comparison to their counterparts (adjusted Hazard Ratio: 0.10, 95% CI of 0.02-0.41; P = 0.027). Conclusion: The study emphasizes the critical role of CP in the ICU, addressing DRPs, and enhancing overall patient care. Furthermore, it highlights the potential impact of pharmacist interventions in improving patient survival outcomes. This underscores the importance of implementing CP services in ICUs across the UAE.